2012
DOI: 10.1134/s1063771012010083
|View full text |Cite
|
Sign up to set email alerts
|

Focused ultrasound as a tool to input sensory information to humans (Review)

Abstract: This review is devoted to the analysis of studies and implementations related to the use of focused ultrasound for functional effects on neuroreceptor structures. Special attention was paid to the stimulation of neuroreceptor structures in order to input sensory information to humans. This branch of medical and phys iological acoustics appeared in Russia in the early 1970s and was being efficiently developed up to the late 1980s. Then, due to lack of financial support, only individual researchers remained at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 47 publications
(72 reference statements)
0
45
0
Order By: Relevance
“…The use of focused ultrasound as a non-invasive method to stimulate neuroreceptor structures in various parts of the human body has been a topic of research since the early 1970s [Gavrilov and Tsirulnikov 2012]. Dalecki et al [1995] first proposed the idea of using water-based ultrasound to create tactile sensations on a finger attached to an acoustic reflector floating at the surface of a water bath.…”
Section: Creating Tactile Sensations Using Focused Ultrasoundmentioning
confidence: 99%
“…The use of focused ultrasound as a non-invasive method to stimulate neuroreceptor structures in various parts of the human body has been a topic of research since the early 1970s [Gavrilov and Tsirulnikov 2012]. Dalecki et al [1995] first proposed the idea of using water-based ultrasound to create tactile sensations on a finger attached to an acoustic reflector floating at the surface of a water bath.…”
Section: Creating Tactile Sensations Using Focused Ultrasoundmentioning
confidence: 99%
“…One of the most intriguing methods for creating tactile sensations in the hand involves focused ultrasound [10], [14]. Gavrilov et al investigated this method as a noninvasive tool for diagnosing diseases that affect the nervous system (e.g., the hearing or the skin).…”
Section: B Ultrasound Stimulation Of Neuroreceptor Structuresmentioning
confidence: 99%
“…Gavrilov et al found that the displacement amplitude was approximately 0.1 micrometer for all threshold intensities and independent of the frequency. However, biological effects (e.g., heating) and the direct action of ultrasound vibrations on nerve fibres could be relevant as well [10].…”
Section: B Ultrasound Stimulation Of Neuroreceptor Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The displacement caused by the shear wave triggers mechanoreceptors within the skin generating a haptic sensation [11]. The second method bypasses the receptors entirely and directly stimulates the nerve fibres [12]. However, this method requires powerful acoustic fields that penetrate the skin, making it unsuitable for applications designed for prolonged use.…”
Section: Ultrasonic Haptic Feedbackmentioning
confidence: 99%